Understanding Flood Vulnerability Issues in Hulu Langat Residential Zone: A Study of Taman Sri Nanding, Hulu Langat, Malaysia - Tasnim, Sharika; Aripin, Srazali; Asif, Nayeem (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Flood vulnerability issues in residential zones in Taman Sri Nanding, Hulu Langat, Malaysia require to be addressed, analyzed and carefully recorded. This is because the residential zones are severely affected and immediately need to implement effective strategies in mitigating flood hazards. However, there are limited research in understanding flood vulnerability issues in residential zone with respect to Taman Sri Nanding, Hulu Langat, Malaysia. There are no framework provided on dealing with the existing flood vulnerability issues in residential zones. The aim of this paper is to understand the flood vulnerability issues in residential zones in Taman Sri Nanding, Hulu Langat, Malaysia and put forward a framework to mitigate the flood hazards.  Qualitative research methodology is adopted for this research through analysing the perspectives of local with open-ended questionnaires. It has been found that there are still more actions required to implement by the local authority in order to provide better living conditions for the residents of Taman Sri Nanding. Moreover, careful considerations should be made for low income group of Taman Sri Nanding, who are the most vulnerable during flood. Hence, it is significant to take into account of the perspectives of local authority for carrying further this research.